Peran Kanwil Kemenkumham Kalimantan Tengah dalam Pelaksanaan Pengharmonisasian Rancangan Produk Hukum Daerah dan Pemanfaatan Aplikasi dalam Penilaian Indeks Reformasi Hukum - Maddolangan, Doaa Risma Diputra; Fransisco, Fransisco; Nugroho, Any (FOCUS, 2025)
This article evaluates the role of the Regional Office of the Ministry of Law and Human Rights (Kanwil Kemenkumham) of Central Kalimantan in implementing the harmonization of regional legal products and its relation to fulfilling the Legal Reform Index (Indeks Reformasi Hukum/IRH) assessment criteria. Legal harmonization is a crucial stage in the formation of local regulations to ensure alignment with the national legal system, while IRH functions as an instrument to measure legal reform efforts at the regional level. This study adopts a juridical-empirical approach, using both legal literature and field documentation as data sources. The findings indicate that the Kanwil has actively and effectively facilitated the harmonization process of draft regional regulations, as reflected by the increasing number of harmonized legal products between 2022 and 2024. However, challenges remain in fulfilling IRH data requirements, particularly due to a lack of technical understanding, limited human resources, and weak administrative coordination at the local government level. It is concluded that the effectiveness of IRH as an evaluative tool largely depends on the synergy between the Kanwil and local governments in developing responsive and accountable legal governance.